Multidimensional Flow Cytometry Techniques for Novel Highly Informative Assays - Gemei, Marica (IntechOpen, 2018)
Flow cytometry's informative potential has been underestimated for many years because of a lack of adequate instruments, automation, reagents, and know-how to approach, integrate, and also substitute other techniques giving single information per assay. In the last decade, flow cytometers have become capable of performing high-throughput screening and high content analysis, evaluating tens of different samples' features in a single run up to 1536 formats on multiple cell populations. The introduction of imaging flow cytometry has filled the gap between flow cytometry and conventional high content imaging screening, putting flow cytometry at the center of many laboratories, which can now cover with a single instrument the vast majority of needs in research programs. The flow cytometry community is a multidisciplinary and diversified group with many different interests and fields of action. These characteristics have prompted the evolution of the techniques, applications, and instruments that allow the use of complex, sophisticated, and standardized and reliable flow cytometric assays in academic and industrial programs.